2010
DOI: 10.1051/0004-6361/201014844
|View full text |Cite
|
Sign up to set email alerts
|

Detecting photons with orbital angular momentum in extended astronomical objects: application to solar observations

Abstract: Context. The orbital angular momentum (OAM) of the photon is a property of light from astronomical objects that has not yet been measured. We propose a method of measuring the OAM spectrum of light from an extended natural source, the Sun. Relating the OAM spectrum of different solar areas to its structures could lead to a novel remote sensing technique. Aims. We present a method for measuring the OAM spectrum of solar photons. Methods. The THEMIS telescope is being used with a novel phase-diversity technique.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Finally, we propose that this technique could be applied to the detection of the ultimate property of light, its orbital angular momentum, from astrophysical objects (Harwit 2003), whose detection, if present, is going to be challenging (Uribe-Patarroyo et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we propose that this technique could be applied to the detection of the ultimate property of light, its orbital angular momentum, from astrophysical objects (Harwit 2003), whose detection, if present, is going to be challenging (Uribe-Patarroyo et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Measuring the POAM spectrum provides an independent measurement of mass and spin. Uribe-Patarroyo et al attempted POAM detection of ±1 POAM transitions by solar photons [14]. Berkhout and Beijersbergen have developed an algorithm to measure POAM with a multipoint interferometer [15].…”
Section: Historymentioning
confidence: 99%
“…Demonstration of the second is more demanding. Whereas observation of astronomical sources relies on measurement of the intensity, wavelength, polarization, or coherence (imaging) of electromagnetic waves to interrogate remote physical systems, for instance gravitational interactions from images, none use the recently enumerated property of POAM (Uribe-Patarroyo et al 2011). We present the first such observations in Sect.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tamburini et al (2011) found that photons could be imparted with orbital angular A&A 556, A130 (2013) momentum through interaction with a Kerr black hole. Also, Uribe-Patarroyo et al (2011) discuss solar photons carrying orbital angular momentum and their use in comparing properties of different solar regions. Berkhout & Beijersbergen (2009) discussed use of a multipoint interferometer as a method of identifying optical vortices in astronomical sources and elsewhere ) described an optical system utilizing two custom optical components for detection of multiple OAM modes simultaneously.…”
Section: Introductionmentioning
confidence: 99%